Improvements in Pain Outcomes in a Canadian Pediatric Teaching Hospital Following Implementation of a Multifaceted, Knowledge Translation Initiative - Lisa M Zhu; Jennifer Stinson; Lori Palozzi; Kevin Weingarten; Mary-Ellen Hogan; Silvia Duong; Ricardo Carbajal; Fiona A Campbell; Anna Taddio (Pain Research and Management)
BACKGROUND: A previous audit performed at a tertiary/quaternary pediatric hospital in Toronto, Ontario, demonstrated suboptimal assessment and treatment of children’s pain. Knowledge translation (KT) initiatives (education, reminders, audit and feedback) were implemented to address identified care gaps; however, the impact is unknown.